Benchmarking on infrastructure maintenance management culture for local authorities in Malaysia / Hamimah Adnan and Zafrul Fazry Mohd Fauzi - Adnan, Hamimah; Mohd Fauzi, Zafrul Fazry (Research Management Institute (RMI), 2012)
In Malaysia, the idea of a scientific and systematic facility audit for performance, effectiveness and efficiency is in its infancy. The awareness level from the society is very low. This has shown that the priority was not carried out for the maintenance works for the available facilities in Malaysia. Furthermore, to make it worse, there are also vandalism activities that take place, which regards to the public facilities. According to Abdullah (2007), heavy punishment should be imposed to the people who caused vandalism and to the officers who fail to carry out proper maintenance of the government facilities towards developing maintenance culture in Malaysia. All government departments should setup their own monitoring unit to carry out routine investigation on the asset and facilities to make sure the facilities are in good working condition.